Socio-Economic Challenges for the Urban Ecosystem: Complex Model of Smart Tourism and Infrastructure - Gevorg Orbelyan (SocioEconomic Challenges)
In order to fill important deficiencies in Yerevan’s current engineering and transportation infrastructure and increase the city's allure as a travel destination, this study aims to develop a new theoretical framework – the Comprehensive Smart Tourism and Infrastructure Model – specifically designed to address the challenges and opportunities unique to Yerevan's urban ecosystem. In contrast to traditional urban planning models, which frequently regard engineering, transportation, and tourism as distinct fields, this integrated model highlights how interdependent these fields are in order to promote a more sustainable and cohesive urban ecosystem. By combining user-centered design, sustainable infrastructure planning, and smart technology, the concept promotes a comprehensive strategy that maximizes environmental sustainability, accessibility, and efficiency. It creates a smooth and appealing experience for both locals and tourists by combining real-time data analytics, dynamic public transit scheduling, and optimized pathways to major tourist destinations. Through this framework, the study offers a blueprint for advancing Yerevan’s digital transformation in ways that align with global smart city trends, thereby promoting sustainable economic growth, social inclusivity, and environmental stewardship. The ultimate goal is to position Yerevan as a pioneering example of how smart infrastructure and tourism can harmonize within an urban ecosystem, creating a thriving, forward-looking city adaptable to evolving demands. In the case of Yerevan, this study also aims to explore how such a model can be customized to fit the city's unique cultural, historical, and infrastructural context. In addition to encouraging sustainable urban expansion, this framework provides a model that may be modified for other communities that are having trouble striking a balance between economic growth and enhancements to the quality of life. This study offers a complete approach that has wide-ranging consequences for investors, policymakers, and urban planners looking to create thriving, resilient communities by developing a model that matches infrastructure development with the demands of contemporary tourism.